1999
DOI: 10.1002/(sici)1097-4547(19990615)56:6<595::aid-jnr5>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Independent mechanisms of potassium clearance by astrocytes in gliotic tissue

Abstract: The "glial impairment hypothesis" states that astrocytes which change from normal into the reactive type lose their ability to clear extracellular K+, which in turn leads to hyperexcitability in the gliotic tissue. As this hypothesis was never proven or disproven, the question of glial efficiency in K+ clearance in gliotic tissue is still controversial, mainly due to the lack of direct measurements of the intracellular K+ concentration of reactive astrocytes. In order to investigate K+ accumulation by glial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 27 publications
2
28
0
1
Order By: Relevance
“…A third channel, ClC-2 has been connected to the more permanent transformation of astrocytes from normal to reactive subtypes (Ferroni et al, 1995). This was demonstrated in cultured cells, but there is also in vivo evidence for a changed chloride conductance after gliosis (Walz and Wuttke, 1999). Reactive gliosis involves an increase in shape and stellation of these astrocytes, but not necessarily proliferation (Jabs et al, 1999).…”
Section: Shape Changesmentioning
confidence: 95%
See 4 more Smart Citations
“…A third channel, ClC-2 has been connected to the more permanent transformation of astrocytes from normal to reactive subtypes (Ferroni et al, 1995). This was demonstrated in cultured cells, but there is also in vivo evidence for a changed chloride conductance after gliosis (Walz and Wuttke, 1999). Reactive gliosis involves an increase in shape and stellation of these astrocytes, but not necessarily proliferation (Jabs et al, 1999).…”
Section: Shape Changesmentioning
confidence: 95%
“…MacVicar et al (1989) found a reversal potential for the GABA A response, in reactive astrocytes of the hippocampal slice, that was more positive than the membrane potential, indicating an active chloride accumulation. Walz and Wuttke (1999) described a resting conductance, whose pharmacological blockade hyperpolarized the membrane of reactive astrocytes in the hippocampal slice, also indicating an active accumulation of chloride. Ballanyi et al (1987) recorded intracellularly from glial cells in slices of guinea-pig olfactory cortex and found evidence for passively distributed chloride ions, contradicting all other in situ and in vitro findings.…”
Section: Cell Chloride Distributionmentioning
confidence: 99%
See 3 more Smart Citations